Hukum Top Up Pembelian Diamond Game Online Anak Dibawah Umur Prespektif Fatwa MUI No:110/DSN-MUI/IX/2017: Studi Kasus Jalan Batang Serangan Kecamatan Padang Tualang Kabupaten Langkat - Devi Amalia Putri Hasibuan; Tetty Marlina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Legal Top Up by Minors for Purchasing Online Game Diamonds Perspective of DSN MUI Fatwa No. 110 of 2017 (Case Study of Jalan Batang attack Padang Tualang District, Langkat Regency) Devi Amalia Putri Hasibuan, North Sumatra State Islamic University, Medan, Indonesia The aim of this research is to find out the view of Islamic law based on the mui fatwa no: 110/dsn-mui/ix/2017 regarding top up online games for minors. This research uses a qualitative method, because this qualitative method places more emphasis on aspects of in-depth understanding of a problem and tends to use analysis, this method is research that is in accordance with field data. Based on these results and discussion, buying and selling diamond top ups is a valid sale and purchase according to Islamic law because it complies with the legal conditions for buying and selling as explained in Islam. Based on this, it can be concluded that mobile legends diamond top ups are included in the Ba'I as Salam category. . In a sale and purchase agreement, payment is made first and delivery of the goods is made afterwards. In language, buying and selling means al-bai, al-tijarah and al-mubadalah.